Multivariate isokinetic asymmetry of the knee and shoulder in elite volleyball players - Markou, S.; Vagenas, G. (European Journal of Sport Science, 2006)
Muscle strength asymmetries have been investigated in athletes under the assumption of their connection to functional discrepancies and injuries. In volleyball, which is a highly asymmetric sport, this assumption becomes a well established research hypothesis. Given the almost complete lack of scientific evidence on this hypothesis, the present study focused on the detailed multivariate quantification of muscle asymmetries in offensive volleyball players. Twenty-four elite athletes (age 24.71±4.44 years, weight 84.62±6.24, height 190.08±5.58) were tested for concentric isokinetic muscle strength (a) of the internal and external rotators of the shoulder and (b) of the quadriceps and hamstrings of the knee at 60o/s. Significant multivariate results were found for absolute (Max-Min) asymmetry in the upper (Hotteling's T2=8.801, F=7.447, P=0.001) and the lower limbs (Hotteling's T2=16.382, F=13.862, P=0.000), for fluctuating asymmetry (Dominant-Non Dominant) in the upper limbs (Hotteling's T2=5.584, F=4.296, P=0.013) and for directional asymmetry (Left-Right) in the lower limbs (Hotteling's T2=3.593, F=3.041, P=0.036). It appears that the upper and lower limbs of offensive volleyball players present significant composite muscle strength asymmetries, which should be taken into consideration in training and rehabilitation.